2009
DOI: 10.1097/pas.0b013e3181ba6db6
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in Situ Hybridization for Distinguishing Nevoid Melanomas From Mitotically Active Nevi

Abstract: Nevoid melanoma may resemble benign compound or intradermal nevi by their silhouette and profile on low power. Higher power usually reveals nuclear atypia, confluence of cells, incomplete maturation and dermal mitotic activity. However, to some extent all of these features maybe seen in benign compound or intradermal nevi and no single criteria can be used to differentiate nevoid melanoma from a benign nevus. The distinction can be particularly problematic in nevi that show mitotic activity and we have noted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
85
1
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 12 publications
2
85
1
4
Order By: Relevance
“…21 It could also be useful if it really changes the treatment of patients, for example, with a thickness greater than 1 or 1.5 mm (according to the protocol), leading to interferon treatment or other adjuvant management such as sentinel node biopsy or adjuvant vaccine therapy. Other FISH applications have been reported to facilitate the differential diagnosis between (I) epithelioid blue nevus and cutaneous metastatic melanoma simulating blue nevus 22 or (ii) nevoid melanomas and mitotically active nevi, 23 (iii) conjunctival nevi from melanomas 24 or (iv) intranodal nevus from metastatic melanoma. 25 In conclusion, a single genetic test allowing the differential diagnosis between benign and malignant ambiguous melanocytic lesions does not yet exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 It could also be useful if it really changes the treatment of patients, for example, with a thickness greater than 1 or 1.5 mm (according to the protocol), leading to interferon treatment or other adjuvant management such as sentinel node biopsy or adjuvant vaccine therapy. Other FISH applications have been reported to facilitate the differential diagnosis between (I) epithelioid blue nevus and cutaneous metastatic melanoma simulating blue nevus 22 or (ii) nevoid melanomas and mitotically active nevi, 23 (iii) conjunctival nevi from melanomas 24 or (iv) intranodal nevus from metastatic melanoma. 25 In conclusion, a single genetic test allowing the differential diagnosis between benign and malignant ambiguous melanocytic lesions does not yet exist.…”
Section: Discussionmentioning
confidence: 99%
“…The aims of our study were first to perform FISH analysis in 43 cases of non-equivocal melanomas (23) and nevi (20) in a training set. Then, we analyzed 113 cases of ambiguous melanocytic tumors provided by six European centers to determine the relevance of such testing by comparison with an expert panel review as well as with patients' clinical course.…”
mentioning
confidence: 99%
“…6 Several proof-of-principle studies showed potential applications of FISH to solve a variety of diagnostic dilemmas in the evaluation of melanocytic tumors, including differentiating blue nevus-like metastasis from blue nevus, mitotically active nevus from nevoid melanoma, and dysplastic nevus from superficial spreading melanoma. [7][8][9][10][11][12] Fluorescence in situ hybridization test abnormalities characteristic of melanoma were identified in lentiginous melanoma supporting this entity as a variant of melanoma.…”
mentioning
confidence: 99%
“…24 Finally, the human RREB1 locus has been found to be amplified in melanoma and is currently an area of intense investigation for its potential in molecular diagnostic testing. [25][26][27][28][29][30] In prostate cancer, RREB1 binds the PSA promoter only in association with AR to repress transcription. 20 In summary, the current literature on RREB1 suggests con-text-dependent phenotypes that may suppress or promote carcinogenesis and tumor progression.…”
mentioning
confidence: 99%